Main Trends in Iberoamerican Clinical Psychology. a Study Based in Scientific Evidence [Principales Tendencias Iberoamericanas en Psicología Clínica. Un Estudio Basado en la Evidencia Científica] - Lillo-Vidal, S (Sociedad Chilena de Psicologia Clinica, 2013)
The availability of techniques that allows the analysis of large quantities of data permits the construction of studies that can characterize the development and evolution of the psychological science through objective parameters, delivering profiles of the main trends. In this article we present a hybrid approach, based on a scientometric analysis and an interpretation of bibliographic communities based on the proportion of shared references (Grawin, 2012) of iberoamerican articles within the Web of Knowledge database. The results show a strong concentration of research on Depression (9%) and Alzheimer (8%), as a heavy use of quantitative and psychometric approaches. While Spain produces 54% of the science and leads 44% of the most influential (cited) production, Latin America produces 37% and leads 13% (Brasil 10%, Chile 1%, Argentina 1%, Colombia 1%). The repercussions of the results are discussed, as the consequences and future applications of these tools for practitioners and researchers. © 2013 by Sociedad Chilena de Psicología Clínica.